Resveratrol-Loaded TPGS-Resveratrol-Solid Lipid Nanoparticles for Multidrug-Resistant Therapy of Breast Cancer: In Vivo and In Vitro Study - Wang, Wenrui; Zhou, Mengyang; Xu, Yang; Peng, Wei; Zhang, Shiwen; Li, Rongjie; Zhang, Han; Zhang, Hui; Cheng, Shumin; Wang, Youjing; Wei, Xinyu; Yue, Chengxu; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Multidrug resistance (MDR) is a serious problem during cancer therapy. The purpose of the present study was to formulate D-α-Tocopheryl polyethylene glycol 1000 succinate-resveratrol-solid lipid nanoparticles (TPGS-Res-SLNs) to improve its therapeutic efficacy against breast cancer. In this study, the solvent injection method was used to prepare the TPGS-Res-SLNs. It was found that the TPGS-Res-SLNs exhibited zeta potential and drug-loading of -25.6±1.3mV and 32.4±2.6%, respectively. Therefore, it was evident that the TPGS-Res-SLNs can increase cellular uptake of chemotherapeutic drugs, induce mitochondrial dysfunction, and augment tumor treatment efficiency by inducing apoptosis. Moreover, it was found that SKBR3/PR cells treated with TPGS-Res-SLNs exhibited significant inhibition of cell migration and invasion, as compared with free resveratrol. In addition, results from in vivo SKBR3/PR xenograft tumor models revealed that TPGS-Res-SLNs has better efficacy in promoting apoptosis of tumor cells owing to high therapeutic outcomes on tumors when compared with the efficacy of free resveratrol. In conclusion, the findings of the present study indicate significant potential for use of TPGS-Res-SLNs as an efficient drug delivery vehicle to overcome drug resistance in breast cancer therapy.